PERAN MASYARAKAT DALAM PENANGANAN KENAKALAN REMAJA DI DUSUN CEMARA DESA SAWAH BARU KECAMATAN KAMPA KABUPATEN KAMPAR - Septi Widia Anggraini; Titi Maemunaty; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the background of the problem, the researcher formulated theproblem. How well is the role of the community in handling juvenile delinquency inCemara Hamlet, Sawah Baru Village, Kampa District, Kampar Regency. The purposeof this study was to find out how well the role of the community in handling juveniledelinquency in Cemara Hamlet, Sawah Baru Village, Kampa District, KamparRegency. This type of research is a descriptive research with a quantitative approach.The sampling technique used is the Simple Random Sampling Technique. The resultsand findings of the research on the role of the community in handling juveniledelinquency in Cemara Hamlet, Sawah Baru Village, Kampa District, Kampar Regencyare classified as very high. Individual treatment indicators, family handling indicators,and group handling indicators.Key Words: Role, Society, Juvenile Delinquency